Effect of media components on hyperhydricity in horticultural crops: A review - Zunazri, Nurhuriyah Hadfina; Kemat, Nurashikin; Ariffin, Norazrin; Rineksane, Innaka Ageng (Korean Society of Plant Biotechnology, 2024)
Abstract Tissue culture of horticultural plants under sterile conditions results in numerous genetically uniform and virus-free plants; hence, the technique is widely used. However, in vitro culture increases the risk of hyper-hydricity, thereby negatively impacting growth quality and causing substantial plant material loss. Hyperhydricity is a physiological, anatomical, and metabolic disturbance caused by various stresses and affects several plant tissues in a highly intricate manner. Hyperhydricity symptoms vary and its occurrence depends on the species or cultivar. This review considers the main physiological, anatomical, bio-chemical, and molecular symptoms in several horticultural plants. The primary determinants of plant hyperhydricity levels in vitro are media components, such as gelling agents and plant growth regulators. Considering these factors, incorporating external additives in media is a viable strategy to tackle hyperhydricity. Nevertheless, not all techniques are universally effective in alleviating hyperhydricity symptoms. Therefore, a thorough examination of hyperhydricity is necessary, and efforts to mitigate hyperhydricity should be complete, intricate, and species-specific.